MEASUREMENT UNITS IN THE ENGLISH AND UZBEK LANGUAGES: LINGUOCOGNITIVE AND LINGUOCULTURAL INVESTIGATION - Nazarov, Behzod (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study delves into the lingvocognitive and linguocultural dimensions of measurement units in English and Uzbek languages, focusing on their roles as cultural artifacts, cognitive tools, and linguistic expressions. Measurement units go beyond their practical use for quantification; they serve as reservoirs of historical knowledge, cultural practices, and cognitive schemas. By analyzing their metaphorical usages, semantic constructions, and cultural narratives, this paper uncovers the nuanced ways in which these units embody societal values, worldviews, and collective identities. The findings offer valuable insights into the linguistic mechanisms through which languages shape, preserve, and communicate cultural heritage, thereby enriching our understanding of cross-cultural interaction and linguistic diversity.